2021
DOI: 10.1177/2374373520981486
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Limitations of Proning Protocol for Nonintubated Patients With COVID-19

Abstract: Proning awake patients with COVID-19 is associated with lower mortality and intubation rates. However, these studies also demonstrate low participation rates and tolerance of awake proning. In this study, we attempt to understand barriers to proning. Medical and dental students surveyed nonintubated patients to understand factors affecting adherence to a proning protocol. Only patients who discussed proning with their medical team attempted the practice. Eight of nine patients who were informed about benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Even though prolonged duration of proning is associated with improved outcome, awake patients cannot tolerate prolonged proning more than 2 to 3 hours. [21,22] Our results are similar to other cohort studies done in the era of COVID-19. Ding and colleagues evaluated the effect of adding awake prone positioning to high-flow nasal cannula oxygen and non-invasive ventilation in 20 patients with moderate-to-severe ARDS.…”
Section: Discussionsupporting
confidence: 90%
“…Even though prolonged duration of proning is associated with improved outcome, awake patients cannot tolerate prolonged proning more than 2 to 3 hours. [21,22] Our results are similar to other cohort studies done in the era of COVID-19. Ding and colleagues evaluated the effect of adding awake prone positioning to high-flow nasal cannula oxygen and non-invasive ventilation in 20 patients with moderate-to-severe ARDS.…”
Section: Discussionsupporting
confidence: 90%
“…Majority of the patients believed it was a difficult posture to maintain and an uneasy maneuver to perform. Another study done on patient's perspective about COVID-19 at Harvard University also showed similar results (11). Other studies also found discomfort, coughing, and uncooperativeness as the main reasons for not performing a proning procedure while awake proning (12,13).…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, Coppo et al 32 found no adverse events related to the APP procedure. In contrast, Shoults et al in United States 38 discovered that all patients rated discomfort as the primary factor for being unable to resume a PP session. Since the beginning of the pandemic, there have been few case reports of patients with COVID‐19 with respiratory difficulties after self‐proning.…”
Section: Discussionmentioning
confidence: 92%